Wide-Bandgap Halide Perovskites for Indoor Photovoltaics - Jagadamma, Lethy Krishnan; Wang, Shaoyang (Frontiers in Chemistry, 2021)
Indoor photovoltaics (IPVs) are receiving great research attention recently due to their projected application in the huge technology field of Internet of Things (IoT). Among the various existing photovoltaic technologies such as silicon, Cadmium Telluride (CdTe), Copper Indium Gallium Selenide (CIGS), organic photovoltaics, and halide perovskites, the latter are identified as the most promising for indoor light harvesting. This suitability is mainly due to its composition tuning adaptability to engineer the bandgap to match the indoor light spectrum and exceptional optoelectronic properties. Here, in this review, we are summarizing the state-of-the-art research efforts on halide perovskite-based indoor photovoltaics, the effect of composition tuning, and the selection of various functional layer and device architecture onto their power conversion efficiency. We also highlight some of the challenges to be addressed before these halide perovskite IPVs are commercialized.